An interspecific hybrid as a tool to study phylogenetic relationships in plants using the GISH technique - Markova, Michaela; Michu, Elleni; Vyskot, Boris; Janousek, Bohuslav; Zluvova, Jitka (Chromosome research, 2007)
We established a new auxiliary phylogenetic approach based on genomic in situ hybridization technique (GISH). We used an interspecific hybrid Silene latifolia x Silene viscosa to compare two different genomes simultaneously on one slide. By using GISH with genomic DNA from another closely related species as a probe, we directly compared the level of relatedness between the genomes of the studied species and parental species. This experimental design enabled us to approximately estimate evolutionary relationships between the genome of tested plant species and genomes of both parental species of the hybrid by using the ratio of intensities of fluorescence signals. We tested this technique in various Silene species and the results were in accordance with the topology of the phylogenetic tree we constructed based on rDNA sequences. The results were also well correlated with phylogenetic distances between species that we estimated from an rDNA-based phylogenetic tree. Our experimental approach could help to improve tree topology and serve as a useful complementary tool in molecular phylogenetic studies in related species.
Keywords: genom rostlinný; Silene; Genome, Plant; DNA, Plant; DNA, Ribosomal; hybridizace in situ fluorescenční; fylogeneze; In Situ Hybridization; DNA rostlinná; ribozomální DNA; Phylogeny; In Situ Hybridization, Fluorescence; hybridizace in situ